Determinants of Piper (Piperaceae) climber composition in a lowland tropical rainforest in New Guinea - Lisner, Aleš (Jihočeská univerzita, 2023)
The study examines the distribution of root climbers from the genus Piper on host trees depending on environmental properties and host tree characteristics in a lowland primary tropical rainforest in Papua New Guinea. More specifically, the study examines the relationship between the climbers' presence and various factors including topography (e.g. slope, altitude), vegetation properties, and host tree characteristics. The findings reveal that Piper climbers tend to avoid higher altitudes, steeper slopes, closed canopy layers, and areas with larger total basal area of host vegetation. The preferences of Piper climbers for certain tree species are primarily influenced by the properties of the host trees, particularly their diameter at breast height (DBH). Additionally, the study suggests that Piper species are more commonly found on rare tree species, possibly due to their preference for larger host tree DBH. The results highlight the non-random association between climbers and their host trees, which is influenced by local environmental conditions. These interactions are likely to have important implications for forest vegetation dynamics and the maintenance of diversity.
Determinants of Piper (Piperaceae) climber composition in a lowland tropical rainforest in New Guinea
Keywords: Piper; climber; tropical forest